Blockchain in Supermarkets: Mitigating the Problem of Organic Waste Generation - Egatz Wozniak, Marcos; Valdés-González, Héctor; Reyes-Bozo, Lorenzo (Society of Visual Informatics, 2021)
This work presents a proposal for a solution to the specific problem of organic waste generated by supermarkets and understood as t merchandise of organic and perishable composition that could not be marketed during its validity period. The goal of this research is to propose a solution based on Blockchain technology in Chile, which would allow an immutable, decentralized, and validated transaction record to be kept. Such a record would enable supermarkets to trace the life cycle of those products that make up organic and perishable merchandise in a transparent, reliable, and scalable way. To this end, the problem is modeled using the Blockchain Hyperledger Fabric platform (an open-source platform started by the Linux Foundation), which is fed with relevant information and data on the status of a representative set of organic merchandise products. At the same time, a qualitative approach is proposed to gather the opinions of executives and logistics operators through semi-structured interviews, and considering a convenience sample. With a sample of 6 executives, it is understood how the proposal is perceived and its applicability in supermarkets and distributors. The data show that both obtaining information and making decisions about it are achieved in a distributed and collaborative way, allowing for reliable and agile traceability, thereby mitigating the low quality of the information provided by the actors that make up the supply chain. This service is perceived as desirable by both customers and operators. The model enables not only horizontal communications between suppliers, distributors, and consumers, but also vertical ones, and thus, ultimately, makes the company's income statement more efficient.